2014
DOI: 10.3732/ajb.1400171
|View full text |Cite
|
Sign up to set email alerts
|

Attracting mutualists and antagonists: Plant trait variation explains the distribution of specialist floral herbivores and pollinators on crops and wild gourds

Abstract: Surprisingly, floral sesquiterpenoid volatiles, which are associated with direct defense, indirect defense, and attraction, rather than defense traits such as cucurbitacins, appeared to drive interactions with both pollinators and floral herbivores across cucurbit taxa. Identifying the relevant plant traits for attraction and deterrence is important in this economically valuable crop, particularly if pollinators and floral herbivores use the same plant traits as cues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 57 publications
2
35
0
1
Order By: Relevance
“…A comparison of twenty cucurbit species and varieties found increased A. vittatum visitation to plants with larger flowers that produced more sesquiterpenoids in their floral scent (Theis et al . ). In that study, sesquiterpenoids were the dominant class of compounds in the most fragrant varieties.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A comparison of twenty cucurbit species and varieties found increased A. vittatum visitation to plants with larger flowers that produced more sesquiterpenoids in their floral scent (Theis et al . ). In that study, sesquiterpenoids were the dominant class of compounds in the most fragrant varieties.…”
Section: Discussionmentioning
confidence: 97%
“…Because adult A. vittatum are sometimes found in flowers, and prior work has demonstrated that their attraction can be explained in part by floral volatiles (Theis et al . ), we also examined Pearson correlations between leaf herbivory and floral VOC traits using the August leaf damage measurements (because few plants were in bloom during the July damage measurements).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs because herbivores and pollinators often use many of the same cues to locate plants (Strauss & Whittall, ). For example, larger flowers (Theis, Barber, Gillespie, Hazzard, & Adler, ), floral displays (Brody & Mitchell, ) and plant volatiles (Theis & Adler, ) can all attract herbivores and lead to direct herbivore‐mediated selection on reproductive traits. Indirect selection by herbivores on reproductive traits can also occur when herbivores alter pollinator behaviour or influence patterns of resource allocation, thereby reducing plant investment in reproductive traits.…”
Section: Introductionmentioning
confidence: 99%
“…Similar dynamics can occur with visual cues [48,49] for example the showy bracts of Dalechampia scandens are attractive to both pollinators and seed predators [48]. Balancing these potential costs of trade-offs from traits with multiple effects will be necessary for selecting appropriate crop breeding strategies [49].…”
Section: Attracting More Of Whatever Pollinators There Arementioning
confidence: 99%